Appreciative Intelligence® in leadership culture transformation: a case study. (1st January 2013) - Lehtimäki, Hanna; Kujala, Johanna; Thatchenkery, Tojo
An internationally operating tyre manufacturer faced a challenge of a critically negative atmosphere caused by an abrupt insecurity in the market and recent layoffs. The Human Resources and Development Department called in a local university research team, and an organisation development (OD) intervention based on Appreciative Intelligence ® and appreciative inquiry was set up to foster leadership culture that would support the international growth of the company. In the process, middle management was interviewed and the top management was engaged in discussing the current and future leadership culture. Middle management defined core values upon which various steps were to be taken to put the goals of future leadership culture in practice. The study shows how a difficult situation can be transferred into an appreciative positive future oriented action.